Composite indicators – methodology and practical aspects - Rukšėnaitė, Jurga (Lietuvos matematikos rinkinys, 2009)
In this paper methodology of construction Composite Indicators is described. Data standardisation and ranking procedures are proposed. Results of modelling irregular component using different ARIMA models are described.